Pelatihan Teknologi dan Etika Profesi dalam dunia Gereja untuk Meningkatkan Kualitas Pelayanan Digital Jemaat - Victor Asido Elyakim P; Yuegilion Pranayama Purba (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2025)
The rapid advancement of information technology has brought significant impacts to various sectors, including religious institutions, compelling churches to adapt to ensure services remain relevant, effective, and transparent. However, adopting technology without a strong foundation of professional ethics risks serious issues, such as information misuse, violations of congregation data privacy, and a decline in service integrity. This community service activity aims to enhance technological competence and understanding of professional ethics for 35 participants, comprising church ministers, administrators, multimedia teams, and youth at the GKPI Sikhem Hall. The activity was conducted over two days, from September 5–6, 2025, utilizing participatory and applicative approaches. Training methods included interactive lectures, demonstrations, hands-on practice in data management and live streaming, discussions on ethical case studies, and digital service simulations. Post-training evaluation yielded positive results: 85% of participants understood basic technology usage , 90% grasped the importance of digital ethics , and 80% were capable of applying technology in actual service. Participants are now able to operate administrative applications, maintain data confidentiality, and practice courteous digital communication. It is concluded that integrating technical competence with professional ethics is crucial; therefore, continuous mentoring is recommended to maintain the consistency of the church's digital service quality.